Safety Net of The Financial System in The Perspective of Indonesian Banking Law - Zulfi Diane Zaini (International Conference On Law, Business and Governance (ICon-LBG), 2013)
The world’s economic conditions has shown a tendency of recession to re-occur in particular indeveloped countries, it is caused due to the worsening global economic and financial conditions thatcould have been worse than the crisis conditions of the last 2008. Related to that global financial crisis,it’s very likely that they have an impact on economic conditions in Indonesia, and the most highlyvulnerable is in banking sector. If this condition (Safety Net) is not anticipated and dealt with seriouslyand comprehensively by the Government, it could have an impact on a deep financial crisis. Thecondition does not only affect the poor aspects of banking liquidity, but also on the solvency andprofitability of the banking institutions.Financial Safety Net is one of the main pillars of economic activity, so that with the specific andexplicit arrangement, the occurrence of bank runs can be pursued and prevented, it can minimize thepossibility of a financial crisis, and it can reduce the frequency and impact of economic contraction inIndonesia.Given the large number of costs that must be borne by the State in the management and resolution ofcrises and the breadth of the impact of the crisis, we need a fine and effective crisis management. A goodand effective crisis management must be supported by a legal framework in the form of legislation andpolicies to deal with the crisis that clearly distinguished set of roles, responsibilities and effectivemechanisms of coordination from each related institution to some monetary authorities in the Safety Net.Crisis management also needs to be supported by the organization and effective leadership so that theycan develop strategies and crisis management measures quickly and effectively in the event of a crisis.